Spot Urine Estimations Are Equivalent to 24-Hour Urine Assessments of Urine Protein Excretion for Predicting Clinical Outcomes - Boon Wee Teo; Ping Tyug Loh; Weng Kin Wong; Peh Joo Ho; Kwok Pui Choi; Qi Chun Toh; Hui Xu; Sharon Saw; Titus Lau; Sunil Sethi; Evan J. C. Lee (International Journal of Nephrology)
Background. The use of spot urine protein to creatinine ratios in estimating 24 hr urine protein excretion rates for diagnosing and managing chronic kidney disease (CKD) predated the standardization of creatinine assays. The comparative predictive performance of spot urine ratios and 24 hr urine collections (of albumin or protein) for the clinical outcomes of CKD progression, end-stage renal disease (ESRD), and mortality in Asians is unclear. We compared 4 methods of assessing urine protein excretion in a multiethnic population of CKD patients. Methods. Patients with CKD (n=232) provided 24 hr urine collections followed by spot urine samples the next morning. We created multiple linear regression models to assess the factors associated with GFR decline (median follow-up: 37 months, IQR 26–41) and constructed Cox proportional-hazards models for predicting the combined outcome of ESRD and death. Results. The linear regression models showed that 24 hr urine protein excretion was most predictive of GFR decline but all other methods were similar. For the combined outcomes of ESRD and death, the proportional hazards models had similar predictive performance. Conclusions. We showed that all methods of assessments were comparable for clinical end-points, and any method can be used in clinical practice or research.